Gender-Differentiated Effects of Physical Education Programs on Health-Related Fitness Parameters - Aditi , Anika Reddy (Journal of Educational Research and Policies, 2025)
The present study was undertaken to evaluate the effect of 6 weeks physical education programme on health related fitness variable of male and female students. For this purpose 15 male and 15 female students of B.P.Ed. 1st year course at LNIPE, Gwalior were selected as subjects for the study. The Health Related Physical Fitness test consisted of Cardiovascular endurance, Muscular endurance, Muscular strength, Flexibility and body composition. The t-ratio was used as statistical measures to find out the significant effect of the physical education programme on the selected health related fitness variables of male and female subjects. The 6 weeks programme of physical education proved significant improvement of cardiovascular endurance, muscular endurance, muscular strength, flexibility and sum of skinfolds (triceps and calf) in case of both male and female subjects. Total body weight and fat weight showed significant decrease for both males and females.